Performance analysis of selective decode and forward protocol with partner selection. (2014) - Muthukumar, S.; Nagarajan, V.
Cooperative diversity is a technique that mitigates fading without additional cost, hardware and complexity. A cooperative diversity system having a source, multiple relays and a destination is considered. The end-to-end symbol error probability (SEP) of a full channel state information (CSI) selection combining scheme for cooperative communication, with selective decode and forward (S-DF) relaying for binary phase-shift keying (BPSK) symbol in a flat Rayleigh fading environment, is derived. Here, the effect of source-to-relay channel is included in the error analysis of cooperative diversity systems with selection combining. The threshold for S-DF is set with ratio factor α . On the basis of the optimised α value, the partner selection is performed. This scheme offers better SEP when compared with conventional selection combining scheme.